Kuat Tarik Tak Langsung Campuran Aspal Beton Dengan Menggunakan Bahan Tambah Serat Karung Goni - Leo Sentosa; Agus Ika Putra; T. Gina Vinola (Jurnal Teknik Sipil, 2012)
The increasing of oil raw price, the quality of asphalt as cementitious materials is getting lower while the traffic loads always increase preferring to the need of transportation. To increase the quality qJbituminous mixture could be conducted by adding additive to asphalt mixture, such as cellulose and polymer materials such as Arbocel, Cellulose Fibres CF-31500, Roadcel, etc. This research was conducted to use local raw materials such as fracegonifiher that was accepted to be new fiber of cellulose to increase biturninOUS mixture ability.This researched was conducted on the mixture ofLASTON of Bina "Varga type III by using asphalt pen 60170 and additive, such as trace goni fiber; it was obtained from Cik Puan market, Pekanharu. The adding offibre contains as 0%, 0,03%, 0,05% and 0, 07% of total weight of mixture. The length offiber were 0,25cm, 0,5 cm and 1 cm.The addition of fiber content on the same fiber length, will increase the value of the optimum asphalt content. Whereas the addition offiber length will decrease the value of the optimum asphalt content. Test of indirect tensile strength of asphalt concrete without goni fiber is amounted 1.404 kg/cm2. The highest value of indirect tensile strength is amounted 1,876k-,-Iciii2i,vhichi,vasohiaiiiedbyaddiiig0.03Y, coiitentgoiiijihei-ivithfihei-leiigthojI cm. This value is 34% higher than the value of indirect tensile strength for asphalt mixture without fiber additive- The lowest of indirect tensile strength is amounted 1, 628 kg/cm2, which was obtained by adding 0.05% content goni fiber with fiber length of 0. 25 cm. This value is 16Y, higher than the value of indirect tensile strength for asphalt mixture without fiber additive.Meningkatnya fiarga minyak mentah mengakibatkan kualitas aspal sebagai bahan perkerasan semakin rendah sedangkan beban lalu limas selalu meningkat sejalan dengan kebutuhan transportasi. Usalia untuk meningkatkan kualitas campuran beraspal dapat dilakukan dengan menambahkan aditif pada campuran aspal, seperti selulosa dan bahan polimer seperti Arbocel, Selulosa Serat CF-3 1500, Roadcel, dan lainnya. Penelitian ini dilakukan menggunakan bahan baku lokal berupa serat karung goni yang diharapkan menjadi serat selulosa baruuntuk meningkatkan kemampuan campuran aspal.Penambahan kadar scratpadapanjatig scratyang sama, akan meningkatkan nilai kadar aspal optimum. Sedangkan penambahan panjang serat akan mengurangi nilai kadar aspal optirniu-n. Uji kuat tarik tidak langsung beton aspal tanpa serat goni adalah sebesar 1.404 kg/cm2. Nilai tertinggi dari kekuatan tarik tidak langsung sebesar 1.876 kg/cm2 yang diperolch dengan tuctrarnbahkan 0,03% scrat goni dengan panj ang scrat dari 1 cm. Nilai ini adalah 34% lebih tinggi dari nilai kuat tarik tak langsung untuk campuran aspal tanpa sera[. Yang terendah dari kekuatan tarik tidak langsung sebesar 1.628 kg/cm2, yang diperoleh dengan menambahkan 0,05% sera[ goni dengan panjang sera[ dari 0,25 cm. Nilai ini adalah 16% lebih tinggi dari nilai kuat tarik tak langsung untuk campuran aspal tanpa serat.